The Influence of Functional and Green Values on Gen Z Green Product Purchases and Entrepreneurial Opportunities - Saputri, Windy Eka; Hurriyati, Ratih; Gunawan, Theresia (Aptisi Transactions On Technopreneurship (ATT), 2024)
This paper investigates Generation Z consumers perspective on the functional value related to their green purchase intentions and decisions, with a particular emphasis on the moderating role of green value in green product purchases. While prior studies have explored functional and green values independently, this research addresses a critical gap by examining how green value moderates the relationship between functional value and green purchasing behavior, offering new insights into sustainable consumption. The study explores how factors such as quality, usability, price, and other indicators of the usefulness of green products influence consumer purchasing behavior and purchase intentions. The research focuses on IKEA customers from the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, Bekasi) and Bandung, gathering data from 580 respondents, which was analyzed using SmartPLS. The findings reveal that functional value directly influences both purchasing intentions and decisions to buy green products. Additionally, the study highlights that green value significantly moderates the relationship between functional value and purchasing decisions, acting as a crucial factor that encourages consumers to purchase environmentally friendly products. These insights suggest that companies should emphasize both functional and green values to effectively boost consumers' intention to purchase green products, particularly among Generation Z.